2013
DOI: 10.1007/s11427-013-4466-4
|View full text |Cite
|
Sign up to set email alerts
|

Advance in herpes simplex viruses for cancer therapy

Abstract: Oncolytic virotherapy is an attractive approach that uses live viruses to selectively kill cancer cells. Oncolytic viruses can be genetically engineered to induce cell lyses through virus replication and cytotoxic protein expression. Herpes simplex virus (HSV) has become one of the most widely clinically used oncolytic agent. Various types of HSV have been studied in basic or clinical research. Combining oncolytic virotherapy with chemotherapy or radiotherapy generally produces synergic action with unclear mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…HSV often infects the mucosa of the mouth, eyes and the human anogenital tract (117). The natural infection of HSV may activate double stranded RNA-dependent protein kinase (PKR) to phosphorylate the eukaryotic initiation factor (eIF)-4A, and subsequently terminate host protein synthesis in order to prevent viral replication (118).…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…HSV often infects the mucosa of the mouth, eyes and the human anogenital tract (117). The natural infection of HSV may activate double stranded RNA-dependent protein kinase (PKR) to phosphorylate the eukaryotic initiation factor (eIF)-4A, and subsequently terminate host protein synthesis in order to prevent viral replication (118).…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…The Ras/mitogen-activated protein kinase signaling pathway is frequently activated in cancer cells, which suppresses PKR and enables γ-34.5-deficient HSV to replicate selectively in cancer cells (119). In addition, the ICP-6 gene encodes the large subunit of ribonucleotide reductase, which is essential for the replication of viral DNA and is highly expressed in rapidly dividing tumor cells (117). ICP-6-mutated HSV is only able to replicate in rapidly dividing cells, but not in quiescent cells (117).…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the α47 promoter increases the expression of MCH-I, thereby improving the tumor antigen presentation. NV1020 NV1020 is derived from HSV-1 with a deletion in UL/S junction (α0, α4 and γ134.5), one copy of UL56, thymidine kinase (TK) gene and addition of the promoter for the gene UL24 and an exogenous copy of TK gene placed under control of the ICP4 promoter enabling its attenuation so that it could replicate only in a tumor cell 45 . Clinical studies with patients having colorectal adenocarcinomas metastatic to the liver showed major reduction in tumor size when administered intravenously in conjugation with chemotherapy 46 .…”
Section: G207 and G47 Deltamentioning
confidence: 99%